Regulatory effects of peptides from the pro and catalytic domains of proprotein convertase subtilisinKexin9 (PCSK9) on low density lipoprotein receptor (LDLR) - Palmer, Heather (University of Ottawa (Canada), 2009)
Proprotein Convertase Subtilisin/Kexin 9 (PCSK9) is the latest member of the PCSK enzyme family that is structurally related to the bacterial subtilisin and the yeast kexin. It plays a major role in the regulation of cholesterol by degrading low-density lipoprotein receptor (LDLR) responsible for the endocytosis of LDL-cholesterol. Thus, there is a great deal of research interest in the development of PCSK9 functional inhibitors which may have potential applications as therapeutic agents for lowering plasma LDL-cholesterol and the associated risk of cardiovascular disease. PCSK9 degrades LDLR by first binding to form a complex and then rerouting to the lysosomal compartment leading to its degradation. In addition it was shown that following the autocatalytic cleavage, the prodomain of PCSK9 remains strongly attached to the mature PCSK9 via its catalytic domain. Owing to these findings, we proposed that selected peptides from hPCSK9 pro and catalytic domains are likely to affect the LDLR binding. Using human hepatic HepG2 and Huh7 cells we showed that the acidic N-terminal and the mid-basic segments of the prodomain enhanced the LDLR protein level significantly, without altering the PCSK9 protein level. The physiologically relevant phoshpho-Ser47 peptide decreased the LDLR protein level suggesting that Ser47-phosphorylation leads to a gain of functional activity of PCSK9. Addition of recombinant PCSK9 to the culture medium decreased the LDLR protein level that was restored by the addition of PCSK931-40, 31-60 or 91-120 peptides. Two catalytic domain peptides PCSK9181-200 and PCSK9368-390 decreased LDLR content confirming their interactions with LDLR. Our study concludes that specific peptides from the pro- and catalytic domains of PCSK9 can regulate LDLR and may be useful for development of novel therapeutics for cholesterol regulation.
Keywords: Chemistry, Biochemistry.